2012
DOI: 10.1021/jf300421m
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Flax Plants To Increase Their Antioxidant Capacity and Improve Oil Composition and Stability

Abstract: The composition of polyunsaturated fatty acids in the tissues is very important to human health and strongly depends on dietary intake. Since flax seeds are the richest source of polyunsaturated acids, their consumption might be beneficial for human health. Unfortunately, they are highly susceptible to auto-oxidation, which generates toxic derivatives. The main goal of this study was the generation of genetically modified flax plants with increased antioxidant potential and stable and healthy oil production. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…All these compounds are regarded as strong antioxidants, and thus it is suggested that they might be involved in protection of fatty acids against oxidation during seed storage and industrial oil extraction. Indeed, engineered linseed plants accumulating phenylpropanoids (mainly hydrolysable tannins) produces oil with a significantly increased quantity (5-fold) of omega-3 fatty acids in comparison to control plants (Zuk et al, 2012). Thus, the obtained results strongly suggest that fatty acid composition and yield depend on the antioxidative status of seeds.…”
Section: Seedcake (Linseed Expeller)mentioning
confidence: 83%
“…All these compounds are regarded as strong antioxidants, and thus it is suggested that they might be involved in protection of fatty acids against oxidation during seed storage and industrial oil extraction. Indeed, engineered linseed plants accumulating phenylpropanoids (mainly hydrolysable tannins) produces oil with a significantly increased quantity (5-fold) of omega-3 fatty acids in comparison to control plants (Zuk et al, 2012). Thus, the obtained results strongly suggest that fatty acid composition and yield depend on the antioxidative status of seeds.…”
Section: Seedcake (Linseed Expeller)mentioning
confidence: 83%
“…This was conducted by down-regulation of the chalcone synthase (CS) gene and redirecting the substrates from the flavonoids into tannin synthesis, phenylpropanoids with higher antioxidant properties (Zuk et al, 2012). This paper is particularly concerned with fiber improvement.…”
Section: Application Of Genetic Engineeringmentioning
confidence: 99%
“…The one example is flax type (called W86) overaccumulating tannins, producing oil with "ideal characteristic" which includes suitable ratio of 6/3 fatty acids recommended by FDA, the presence of tocopherols and water soluble antioxidants which guarantee oil stability (Zuk et al, 2012). Another example is the flax type (called W92) overproducing phenolics whose fibers were successfully used for preparing wound dressing for chronic wound healing (Skórkowska-Telichowska et al, 2011).…”
Section: The Opportunity For Biotechnology To Renew Flax Market Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Abbadi et al (2004) reported a high accumulation of 20C PUFAs including ARA and EPA in transgenic flaxseed after transformation with genes encoding acyl-desaturases and acyl-elongases from Physcomitrella patens, Borago officinalis and Phaeodactylum. Zuk et al (2012) observed significantly increased PUFA levels in plants transformed with a chalcone synthase gene from Petunia hybrida. Polyakov et al (1998) transformed fibre flax cultivars and analysed the expression of introduced genes coding NPT II and GUS.…”
Section: Modification Of Fatty Acid Content and Composition In Flaxmentioning
confidence: 77%